Penyelundupan Hukum dalam Transaksi Tanah oleh WNA: Studi Putusan PN Gianyar No. 259/2020 - Harahap, Nur Aini; Purba, Hasim; Tony (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the practice of legal smuggling in land ownership by foreign nationals (FNs) through nominee agreements, with a specific focus on District Court Decision Number 259/PDT.G/2020/PN.Gin in Gianyar. The research examines how this practice violates the provisions of the Indonesian Basic Agrarian Law (UUPA), which strictly limits freehold land ownership to Indonesian citizens, and assesses the role and responsibility of Notaries and Land Deed Officials (PPAT) in facilitating such transactions. The research employs a normative juridical method with a descriptive-analytical approach. Data were collected through a literature study involving primary, secondary, and tertiary legal materials, and analyzed qualitatively. The findings reveal that nominee agreements used by foreign nationals to acquire freehold land constitute a form of legal smuggling, facilitated through deeds executed before Notaries and PPATs. In the case examined, the court ruled that such an agreement was null and void by law as it contradicted Article 1335 of the Indonesian Civil Code and the core principles of agrarian law.Theoretically, this study reinforces the principle of legality in contract law and emphasizes that any legal manipulation contravening agrarian norms cannot serve as a valid legal basis for land ownership. The findings underline the importance of regulatory oversight of nominee practices and the strategic role of public officials in upholding the integrity of land law in Indonesia.